Superior diagnostic performance of Grocott methenamine silver staining in pulmonary cryptococcosis: a multicenter, large-sample cohort study - Wang, Suijing; Lai, Jieyi; Zheng, Chengyou; Yang, Pengfei; Zhou, Zhengyi; Wu, Haibo; Huang, Mayan; Zhang, Xinke; Xiao, Yongbo; Chen, Jierong; Ma, Chao; Chen, Keming; et al. (Frontiers in Microbiology, 2025)
IntroductionIn the histopathological diagnosis of pulmonary fungal infections, particularly pulmonary cryptococcosis, the diagnostic performance of different staining techniques varies significantly, often confounding pathologists. This study aims to systematically analyze Grocott methenamine silver (GMS), periodic acid-Schiff (PAS), and alcian blue (AB) staining methods to establish evidence-based diagnostic criteria.MethodsWe incorporated histopathological data from 790 cases of pulmonary cryptococcosis that were definitively diagnosed in six tertiary hospitals. Multidimensional statistical analyses were performed to evaluate the performance of GMS, PAS, and AB staining methods.ResultsGMS staining had a 100% positive diagnostic rate among all cohorts, which was significantly higher than that of PAS staining (93.7%, p < 0.001) and AB staining (75.4%, p < 0.001). Further statistical analyses indicated that GMS was superior to PAS and AB in detecting the number of cryptococci and in demonstrating the staining intensities for both intracellular and extracellular cryptococci (p < 0.001 for all comparisons). In the necrotic cores and peri-necrotic margins of granulomas, GMS more clearly localized cryptococci and detected a higher fungal burden. Even in colonies with minimal polysaccharides in fungal cell walls and capsules, GMS exhibited high sensitivity and provided clear visualization.ConclusionGMS staining is the best method for diagnosing pulmonary cryptococcosis because of its high sensitivity and excellent visualization capabilities. Using GMS alone can meet the requirements for diagnostic accuracy, and we recommend GMS as the gold standard for histopathological confirmation of pulmonary cryptococcosis.